Removal of dyes from water using crosslinked aminomethane sulfonic acid based resin - Kaner, Damla; Sarac, Ayfer; Senkal, Bahire Filiz (SPRINGER, 2010)
A new polymeric resin with amino sulfonic acid pendant functions has been prepared for the extraction of acidic and basic dyes from water. Beaded polymer supports were prepared by suspension polymerization of vinyl benzyl chloride (0.9 mol) and ethylene glycol dimethacrylate (0.1 mol). The resulting copolymer beads were modified with amino methane sulfonic acid. The dye adsorption capacity of the resin was found as 0.16 g dye/g resin for ramazol black and 0.15 g dye/g resin for crystal violet. The pH depending measurements and dye sorption kinetics of the resin were also investigated.
Keywords: Dye removal; Polymeric sorbent; Poly (vinyl benzyl chloride); Resin; REACTIVE DYES; POLYSTYRENE RESIN; AQUEOUS-SOLUTIONS; WASTE-WATER; RICE HUSK; ADSORPTION; EQUILIBRIUM; WASTEWATERS; DYESTUFFS; CHITOSAN; Engineering; Environmental Sciences & Ecology; Public, Environmental & Occupational Health; Water Resources